Auroral electrojets during severely disturbed geomagnetic condition on 24 August 2005 - Singh, Anand K.; Sinha, Ashwini K.; Saini, S.; Rawat, Rahul (My University, 2015)
Very intense and highly dynamic eastward and westward currents flowing in the auroral ionosphere are traditionally monitored by the auroral electrojet indices – View the MathML source, respectively. In this study we show that on occasions of intense magnetic activity, entire auroral oval could be dominated by the westward flowing currents, which lead to depression not only in AL index but also in supposedly positive AU index. During negative AU intervals, there could be up to ∼20% underestimation of the total maximum intensity of the auroral electrojet represented by View the MathML source). A detailed investigation of a well-studied extremely intense event of 24 August 2005 has been carried out. Global prevalence of the westward auroral electrojet was clearly observed at the auroral latitudes during the unusually intense substorm (AL∼-4000 nT) on the day. Moreover, along the noon meridian westward electrojet appeared in the auroral region whereas eastward electrojet shifted towards lower latitudes. This paper emphasizes that intense substorms are represented better by AL index than AE index.
Keywords: Storm; Substorm; Auroral electrojets